Relationship Between Anxiety and Asthma Control Among Pregnant Women with Asthma - Aenah, Winda; Bakhtiar, Arief; Frety, Endyka Eyre (Journal of Maternal and Child Health, 2023)
Background: Asthma is a disorder of the airways in the form of chronic inflammation (inflammation). Pregnancy with a history of asthma certainly feels uncomfortable and can interfere with daily activities, this is what will cause an anxiety response. Anxiety in pregnancy with a history of asthma will certainly have an influence on asthma control in pregnant women, so there is a need for research on this case. The purpose of this study was to determine the relationship between anxiety levels and the incidence of asthma control in pregnant women with asthma comorbidities at Airlangga University Hospital, Surabaya. Subjects and Method: This was an analytic observational study with cross sectional design. The sample in this study were pregnant women with comorbid asthma at Airlangga University Hospital who visited from January to March 2022 and sample selection used a purposive sampling method. The dependent variable is the level of asthma control. The independent variable is the level of anxiety. The research instrument used a Hamilton Anxiety Rating Scale (HARS) and Asthma Control Test (ACT) questionnaire. Data were analyzed using the Spearman Correlation test.   Results: There was a positive and moderate relationship between anxiety and asthma control in pregnant women with asthma comorbidities. Pregnant women with comorbid asthma who experienced severe anxiety had total control of asthma control, and this result was statistically significant (r= 0.41; p= 0.002). Conclusion: There is a significant relationship between anxiety and the level of asthma control in pregnant women with asthma comorbidities at Airlangga University Hospital. Keywords: pregnancy, anxiety, asthma control. Correspondence: Winda Aenah. Midwifery Program Study, Faculty of Medicine, Universotas Airlangga,Indonesia. Jl. Mayjen Prof.Dr. Moestopo No. 47, Pacar Kembang, Tambaksari, Surabaya 60132, East Java. Email: winda.aenah-2019@fk.unair.ac.id. Mobile: +6285785099130.